2017
DOI: 10.5530/ijper.51.2.23
|View full text |Cite
|
Sign up to set email alerts
|

A Supply of Information towards Academic Stress in Students Pursuing Pharmacy Programme in India – An Exploratory Study

Abstract: Challenging stimulus can lead to positive outcomes such as motivation and improved task performance while threatening ones or distress can result in anxiety, depression and stress. The current prospective observational exploratory study was designed to assess the stressors causing academic stress in pharmacy students of India. In the study a standard stressors scale was designed with 35 questionnaires as open -ended questions to assess both the positive and negative responses of the student participants in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Academic stress has been well noted among pre-university and university students [ 11 ]. Across the globe, studies carried out at universities in Thailand, Malaysia, the United Kingdom, and India observed academics as a perceived stressor among students [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Scientific literature indicates that stress is quite prevalent in Saudi academia, particularly in female students studying health-related courses [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Academic stress has been well noted among pre-university and university students [ 11 ]. Across the globe, studies carried out at universities in Thailand, Malaysia, the United Kingdom, and India observed academics as a perceived stressor among students [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Scientific literature indicates that stress is quite prevalent in Saudi academia, particularly in female students studying health-related courses [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Academic stress among college and university students has been well documented [27]. Studies conducted at universities in Thailand, Malaysia, the United Kingdom and India found that students around the world perceive academics as a stressor [28][29][30][31][32][33][34]. According to scienti c research, stress is fairly common in Saudi academia, especially among female students pursuing health-related courses [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…This is reported worldwide as studies conducted in universities of the UK, India, Malaysia, and Thailand also highlighted that examinations and amount of taught content throughout the academic session were perceived as stressors by students. [ 16 17 18 24 25 26 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, counseling by pharmacists regarding self-care may help in promoting responsible self-medication among students. [ 26 28 ] Further investigation is needed to identify the reasons for relatively higher stress level among students studying in health cluster colleges as compared to nonhealth cluster college students. A self-evaluation and quality assurance process may be initiated to have an insight into the curriculum design that might help in restructuring the courses so as to decrease academic load and subsequently academic stress.…”
Section: Onclusionmentioning
confidence: 99%